Design of a Web Based Information System to Manage Delivery Activities - Aniza Nur Madyanti; Nessa Ananda; Monanda Wandita Rini; Samsul Rizal (Jurnal Rekayasa Sistem & Industri, 2023)
The information and data processing in logistics activities are necessary for improving companyperformance. One logistics activity that needs to be managed is the shipment of goods. Some companiesmanually record and store shipment data, facing issues related to accuracy and pace. This research aims todesign a web-based goods delivery information system for recording, storing, processing, and reportingshipments swiftly and faultlessly. The system is designed using stages in the Waterfall model, includinganalysis of needs, design, coding, and testing. The result is a web-based goods delivery application that canmanage shipment activity data automatically and in real-time, reducing errors in recording and processingtime. The system can also generate shipping documents, such as waybills and invoices, automatically andcan be printed directly. Furthermore, it provides automatic real-time shipment reports, allowing monitoringof delivery performance through a dashboard on the main page of the application. This information systemcan assist companies in managing shipment activities.